モンゴル・アルタイ Potanin氷河の質量収支 - 紺屋, 恵子; 門田, 勤; 中澤, 文男; 矢吹, 裕伯; Davaa, Gombo; Purevdagva, Khalzan; 大畑, 哲夫; Keiko, Konya; Tsutomu, Kadota; Fumio, Nakazawa; Hironori, Yabuki; Tetsuo, Ohata (2010)
第33回極域気水圏シンポジウム 11月30日（火） 国立極地研究所 ２階大会議室 conference object